2011
DOI: 10.1073/pnas.1100764108
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into Myc stabilization in breast cancer involving aberrant Axin1 expression

Abstract: High expression of the oncoprotein Myc has been linked to poor outcome in human tumors. Although MYC gene amplification and translocations have been observed, this can explain Myc overexpression in only a subset of human tumors. Myc expression is in part controlled by its protein stability, which can be regulated by phosphorylation at threonine 58 (T58) and serine 62 (S62). We now report that Myc protein stability is increased in a number of breast cancer cell lines and this correlates with increased phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 38 publications
11
85
0
Order By: Relevance
“…Previously, we have shown that pS62-MYC, a more stable and active form of MYC, is highly expressed in breast cancers (4,7). In addition, we found that expression of AXIN1, which nucleates the MYC degradation complex, is decreased in some breast tumors (4).…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…Previously, we have shown that pS62-MYC, a more stable and active form of MYC, is highly expressed in breast cancers (4,7). In addition, we found that expression of AXIN1, which nucleates the MYC degradation complex, is decreased in some breast tumors (4).…”
Section: Resultsmentioning
confidence: 72%
“…In addition, we found that expression of AXIN1, which nucleates the MYC degradation complex, is decreased in some breast tumors (4). To investigate additional mechanisms that lead to MYC overexpression, we focused on SET and CIP2A, two oncogenic cellular inhibitors of PP2A, the phosphatase that removes S62 phosphorylation to destabilize MYC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations